Plan de negocios para la creación de un restaurante de gastronomía tradicional en la parroquia Sígsig, provincia del Azuay. - Llanos Loja, Andrea Elizabeth (2024)
Traditional restaurants are those establishments that offer a wide variety of typical food and drinks prepared with traditional techniques and local ingredients in a welcoming atmosphere, representing the local culture of a given territory. The general objective of this research project was to develop a business plan for the creation of a traditional restaurant in the parish of Sígsig, province of Azuay, and two specific objectives were established: to carry out a diagnosis of the current tourism situation in the canton of Sígsig and to develop a business plan using the CANVAS method for the creation of a traditional restaurant. The work required the application of deductive, analytical-synthetic and descriptive methods and techniques such as direct observation, interviews with key actors, surveys of the tourist population of the canton of Sígsig GEOVIT and the economically active population of the canton of Cuenca for a potential demand, population and sample sizes. In the elaboration of the first objective, methodologies such as the PESTEL technique were applied for the study of the external political, economic, social, technological, ecological, legal and tourism factors of the study area, the matrix of the summary sheets of the Ministry of Tourism and finally the matrix of strategies of internal and external factors. The results obtained in the project are the acceptance for the creation of this type of restaurant due to the fact that there is a demand for traditional gastronomy, in addition, both the strengths and the opportunities are greater than the weaknesses and threats, so it was necessary to propose strategies to minimize them. For the restaurant an initial investment of $215,351 dollars is necessary, in the financial evaluation, the net present value is $281,37 dollars, the internal rate of return is 53.89% and the payback period of the investment is 2 years and 11 months.